The statistical characteristics of meter-size meteoroids in the earth atmosphere - Черногор, Л. Ф.; Шевелев, Н. Б. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2018)
This paper deals with 722 celestial body parameter statistics retrieved from the NASA database. The cumulative distributions of the yearly number of events for the initial kinetic energy, the radiated energy, and their mass are plotted. The corresponding empirical relations are fitted. The discrepancy between the observational data and their approximation is explained. The laws confirming the statistics for the larger number of celestial bodies intruding into Earth’s atmosphere are determined.